Virtual Reality and the Mediation of Acute and Chronic Pain in Adult and Pediatric Populations: Research Developments - Hadjiat, Yacine; Marchand, Serge (Frontiers in Pain Research, 2022)
The use of virtual reality (VR) in the mediation of acute pain in adults has shown real benefit to patients for the past 20 years. This review of the literature provides a descriptive synthesis of the types of VR technology, the mechanisms by which VR mediates pain, and a history of early research in the area. A review of the use of VR to mediate chronic pain in adults, and both acute and chronic pain in pediatric populations follows. The studies reviewed provide mixed results and it is noted that many studies have small sample sizes, are case studies, and do not control for extraneous variables such as the dosage and type of VR technology used. Although VR is an exciting area of inquiry that promises to yield multiple applications, there is a necessity to conduct larger random controlled trials to better understand the use cases for which VR is most effective.